ANALYSIS OF AL-FARABI'S MANUSCRIPT TREATISES STORED IN THE LEIDEN LIBRARY (Journal of Oriental Studies, 2023)
The article raises the question of paying attention to the extant handwritten treatises of Abu Nasr al-Farabi. The necessity of determining their exact number and full name is emphasized. Attention is also drawn to the fact that a number of al-Farabi's treatises, which were not included in scientific circulation, have been preserved only in handwritten form.This article defines the total number and titles of handwritten treatises belonging to al-Farabi, stored in the library of Leiden University in the Netherlands, and also clearly indicates their registration numbers in the library. It is noted that among these treatises there is a treatise that has not yet entered scientific circulation and has not been translated into Kazakh.Described in Maqālāt ar-Rafīʿa ʿIlm Uṣūl fī aṭ-Ṭabīʿa (registration number: Or.2930); ʿUyūn al-Masāʾil (registration number: Or.184:13); Fī mā yanbaġī an yuqaddama taʿallum qabla al-falsafa (registration number: Or. 184:7) copies of the first and last pages of these 3 (three) manuscripts of the treatise are attached.During the preparation of the article, methods of collection, grouping, differentiation, comparison, translation from the original, citation, wording, etc. of unique manuscripts belonging to al-Farabi were used.Key words: al-Farabi, manuscript, original text, translation, description.